1993
DOI: 10.1111/j.1365-3040.1993.tb00899.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increased CO2 concentration and temperature on growth and yield of winter wheat at two levels of nitrogen application

Abstract: Winter wheat {Triticum aestivum L., cv. Mercia) was grown in chambers under light and temperature conditions similar to the UK field environment for the 1990/1991 growing season at two levels each of atmospheric CO2 concentration (seasonal means: 361 and 692 |imol mol"^), temperature (tracking ambient and ambient +4 °C) and nitrogen application (equivalent to 87 and 489 kg ha* total N applied). Total dry matter productivity through the season, the maximum number of shoots and final ear number were stimulated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
124
2
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(146 citation statements)
references
References 30 publications
16
124
2
1
Order By: Relevance
“…Studies with bean (Jifon and Wolfe 2005), potato (see Peet and Wolfe 2000), and winter wheat (Mitchell et al 1993) have shown that increasing CO 2 cannot compensate for yield losses associated with negative heat stress effects on flower, fruit, or seed development. Thus, for heat-sensitive crops, much of the potential CO 2 beneficial effect on crop growth will not be realized if CO 2 increase is concomitant with an increase in frequency of high temperature stress as projected for the NE (Fig.…”
Section: Rainfall and Droughtmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with bean (Jifon and Wolfe 2005), potato (see Peet and Wolfe 2000), and winter wheat (Mitchell et al 1993) have shown that increasing CO 2 cannot compensate for yield losses associated with negative heat stress effects on flower, fruit, or seed development. Thus, for heat-sensitive crops, much of the potential CO 2 beneficial effect on crop growth will not be realized if CO 2 increase is concomitant with an increase in frequency of high temperature stress as projected for the NE (Fig.…”
Section: Rainfall and Droughtmentioning
confidence: 99%
“…Many important grain crops, such as field corn, wheat, and oats tend to have lower yields when summer temperatures increase because the plant developmental cycle is speeded up and the duration of the grain-filling period is reduced (Rosenzweig and Hillel 1998;Mitchell et al 1993). In addition, an increase in the frequency of day and/or night temperatures exceeding a high temperature threshold (varies with species, but typically between 27-35°C, Peet and Wolfe 2000) will negatively affect flowering, fruit set, and/or seed production of many crop species.…”
Section: Temperaturementioning
confidence: 99%
“…Under rain-fed and water-and nitrogen-limited conditions, it was found that seasonal temperature increases of up to 2 • C increased yields by avoiding water and heat stress at the end of the season 21 . However, other experimental evidence suggests that increased temperature has negative impacts regardless of water 22 ( Supplementary Figs 15 and 16) and N supply 23 (Supplementary Fig. 17).…”
mentioning
confidence: 99%
“…In two studies with Calluna vulgaris (Whitehead, Caporn & Press 1997) and wheat (Wong & Osmond 1991), there was still a major increase in biomass in elevated [CO 2 ] in nitrogen-limited plants. However, in many other studies with a range of species including wheat (Hocking & Meyer 1991a;Mitchell et al 1994;McKee & Woodward 1994;Rogers et al 1996b;Fangmeier et al 1997), cotton (Wong 1979;Rogers et al 1996a), Xanthium occidentale (Hocking & Meyer 1985), Eucalyptis grandis (Conroy, Milham & Barlow 1992), oak seedlings (Norby, O'Niell & Luxmore 1986), loblolly pine seedlings (Gebauer, Reynolds & Strain 1996) and Influence of nitrogen on response to elevated CO 2 in tobacco 1179 birch (Pettersson et al 1993) the relative and absolute stimulation of growth in elevated [CO 2 ] was much smaller in nitrogen-limited plants than in well-fertilized plants. In soybean (Sionit 1983), Agrostis capillaris and Nardus strictus (Bowler & Press 1996), loblolly pine (Griffin, Thomas & Strain 1993;Thomas, Lewis & Strain 1994;Johnson, Ball & Walker 1995), chestnut (El-Kohen & Mousseau 1994) and several woody species (Eamus & Jarvis 1989) (Wong 1979;Hocking & Meyer 1991a, 1991bPettersson et al 1993;Rogers et al 1993;McKee & Woodward 1994;Jacob et al 1995;Poorter et al 1997), elevated [CO 2 ] should promote more growth in nitrogen-limiting conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In two studies with Calluna vulgaris (Whitehead, Caporn & Press 1997) and wheat (Wong & Osmond 1991), there was still a major increase in biomass in elevated [CO 2 ] in nitrogen-limited plants. However, in many other studies with a range of species including wheat (Hocking & Meyer 1991a;Mitchell et al 1994;McKee & Woodward 1994;Rogers et al 1996b;Fangmeier et al 1997), cotton (Wong 1979;Rogers et al 1996a), Xanthium occidentale (Hocking & Meyer 1985), Eucalyptis grandis (Conroy, Milham & Barlow 1992) (Wong 1979;Hocking & Meyer 1991a, 1991bPettersson et al 1993;Rogers et al 1993;McKee & Woodward 1994;Jacob et al 1995;Poorter et al 1997), elevated [CO 2 ] should promote more growth in nitrogen-limiting conditions. Although the increased nitrogen use efficiency in elevated [CO 2 ] is partly due to a decrease of the nitrate content (Purvis et al 1974; Yelle, Gosselin & Trudel 1987;Hocking & Meyer 1985;Hocking & Meyer 1991b;Poorter et al 1997), growth in elevated [CO 2 ] also typically leads to a lower organic nitrogen concentration (see above), indicating that organic nitrogen use efficiency is also improved (Wong 1979;Curtis et al 1989;Garbutt et al 1990;Coleman et al 1991;Hocking & Meyer 1991a, 1991bColeman & Bazzaz 1992;Gries et al 1993;Pettersson et al 1993;Pettersson & MacDonald 1994;Körner & Miglietta 1994;...…”
Section: Introductionmentioning
confidence: 99%